Consideration of hydrodynamic forces in determining the force factors acting operating elements of a scroll compressor - V. A. Pronin; A. V. Kovanov; E. N. Mikhailova; A. Yu. Zhilkin (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение")
Increasing the efficiency of compressor equipment is an important task, the solution of which contributes to the rational use of economic resources and improvement of the environmental situation. In this regard, the task of improving the characteristics of oil-filled scroll compressors is relevant. The purpose of this study is to clarify the degree of influence of hydrodynamic forces on the working elements of a scroll compressor during the movement of a movable scroll. When the tangential gap is filled with oil and the spiral moves during operation, we can talk about the influence of the hydrodynamic lifting force, on the basis of which the operating principle of hydrodynamic plain bearings is implemented. As a result, the hydrodynamic forces in the tangential gap of a scroll compressor and the possibilities of applying the theory of hydrodynamic lubrication for its calculation are investigated.